The in vitro mechanism of Vaspinregulates the proliferation and steroidogenesis of rat lutein cells - Xiao-wen Fu; Ling Liu; Xiao-yu Zhu; Jian-jun Wang (Gynecological Endocrinology)
Objective Stable luteal cell function is an important prerequisite for reproductive ability and embryonic development. However, luteal insufficiency seriously harms couples who have the desire to have a pregnancy, and the most important thing is that there is no complete solution. In addition, Vaspin has been shown to have regulatory effects on luteal cells, but the complex mechanisms involved have not been fully elucidated. Therefore, this study aimed to explore the effect of Vaspin on rat luteal cells and its mechanism.Methods Granulosa lutein cells separated from the ovary of female rats were incubated for 24h with gradient concentrations of Vaspin, and granulosa lutein cells incubated with 0.5% bovine serum albumin were used as controls. The proliferation, apoptosis, angiogenesis, progesterone (P4) and estradiol (E2) were detected by CCK-8, Anneixn-FITC/PI staining, angiogenesis experiment and ELISA. Western blot was applied to observe the expression levels of proteins related to cell proliferation, apoptosis, angiogenesis and MEK/MAPK signaling pathway.Results Compared with the Control group, Vaspin could significantly up-regulate the proliferation of granulosa lutein cells and reduce the apoptosis. Moreover, Vaspin promoted the angiogenesis of granulosa lutein cells and the production of P4 and E2 in a concentration-dependent manner. Furthermore, Vaspin up-regulated the CyclinD1, CyclinB1, Bcl2, VEGFA and FGF-2 expression in granulosa lutein cells, and down-regulated the level of Bax. Also, Vaspin increased the p-MEK1 and p-p38 levels.Conclusion Vaspin can up-regulate the proliferation and steroidogenesis of rat luteal cells and reduce apoptosis, which may be related to the influence of MEK/MAPK activity.